2019
DOI: 10.1002/csr.1846
|View full text |Cite
|
Sign up to set email alerts
|

Corporate sustainability and stakeholder value trade‐offs in project selection through optimization modeling: Application of investment banking

Abstract: This study presents a new optimization model for quantitative sustainability measurement in net present value estimation process of corporate investments. Proposed model presents an innovative perspective for the transformation of the logic behind traditional investment project selection practices to the sustainable project selection in corporations. By using the proposed model, it is possible that investors' can find positive sustainability trade‐offs without harming returns on investment. A case study is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…This work extends prior studies analyzing CS in the banking sector. This literature focuses on different areas, such as the role of banks in sustainable development (Coulson, 2009; Forcadell & Aracil, 2017b; Lundgren & Catasús, 2000; Raut, Cheikhrouhou, & Kharat, 2017), CS as a driver of bank performance (Aras, Tezcan, & Kutlu Furtuna, 2018; Gangi, Mustilli, & Varrone, 2018; García‐Sánchez & García‐Meca, 2017; Weber, 2012; Weber, Fenchel, & Scholz, 2008) and bank reputation (Dell'Atti et al, 2017; Forcadell & Aracil, 2017a; Pérez and Rodríguez, 2015), how institutional settings determine banks' sustainable policies (Gallego‐Álvarez & Pucheta‐Martínez, 2019), or banks' stakeholder management (Kudratova et al, 2019; Venturelli, Cosma, & Leopizzi, 2018). Against this backdrop, we complement existing research on sustainable banking by highlighting the complementarities between CS and digitalization in leveraging their individual outcomes with regard to boundaries and scope.…”
Section: Discussionmentioning
confidence: 99%
“…This work extends prior studies analyzing CS in the banking sector. This literature focuses on different areas, such as the role of banks in sustainable development (Coulson, 2009; Forcadell & Aracil, 2017b; Lundgren & Catasús, 2000; Raut, Cheikhrouhou, & Kharat, 2017), CS as a driver of bank performance (Aras, Tezcan, & Kutlu Furtuna, 2018; Gangi, Mustilli, & Varrone, 2018; García‐Sánchez & García‐Meca, 2017; Weber, 2012; Weber, Fenchel, & Scholz, 2008) and bank reputation (Dell'Atti et al, 2017; Forcadell & Aracil, 2017a; Pérez and Rodríguez, 2015), how institutional settings determine banks' sustainable policies (Gallego‐Álvarez & Pucheta‐Martínez, 2019), or banks' stakeholder management (Kudratova et al, 2019; Venturelli, Cosma, & Leopizzi, 2018). Against this backdrop, we complement existing research on sustainable banking by highlighting the complementarities between CS and digitalization in leveraging their individual outcomes with regard to boundaries and scope.…”
Section: Discussionmentioning
confidence: 99%
“…Sustainable business models examine a spectrum of stakeholders' interests, including environmental and social issues [31]. The concept of corporate sustainability gives the potential to be more embracing in terms of the company benefits, as well as the social and environmental implications for stakeholders [32].…”
Section: The Background Of the Researchmentioning
confidence: 99%
“…Kudratova et al developed a corporate sustainability driver model by integrating sustainability cost measurements into the traditional selection of projects. The authors found that sustainability cost estimation in traditional project selection methods produces positive returns on investment and produce positive trade-off results for both the environment and sustainability [17]. They also proposed a sustainability optimization model that considered sustainability cost and reinvestment strategy.…”
Section: Sustainability Costmentioning
confidence: 99%